PENGARUH PROMOSI PENJUALAN DAN CELEBRITY ENDORSER TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK MUSTIKA RATU - FAJRIA, IIN (Jurnal Ilmu Manajemen (JIM), 2018)
The main target of the company is one of them to maintain the continuity of business, so that the sales turnover is always increasing. Efforts made by the company are to develop its marketing strategy. One of the ways used by the company is to use sales promotion and celebrity endorser. Mustika Ratu is one of the cosmetics company in Indonesia that has been doing sales promotion and celebrity endorser. Although the company has made an attractive sales pitch and uses celebrity endorsers to attract its customers, its sales have dropped dramatically. Therefore, companies need to design sales promotion and celebrity endorsers are good in increasing sales. This research uses conclusive research. Sampling technique used is non-probability sampling with 210 samples. The population in this research is all consumers who ever bought, using Mustika Ratu cosmetics, and know the promotion done Mustika Ratu and celebrity endorser Mustika Ratu cosmetics. Scale used in this research that is using likert scale. The measuring instrument used is a questionnaire. The analytical tool used multiple linear regression analysis with SPSS 18 program. The results showed that sales promotion and celebrity endorser variables have a positive and significant influence, but sales promotion variables have greater influence on purchasing decisions, compared with celebrity endorser. Keywords: sales promotion, celebrity endorser, purchase decision.